2017
DOI: 10.1186/s12887-017-0894-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of objectively measured sedentary time in 10- to 12-year-old Belgian children: an observational study within the ENERGY-project

Abstract: BackgroundThis study examined the frequency of and differences in sedentary bouts of different durations and the total time spent in sedentary bouts on a weekday, a weekend day, during school hours, during after-school hours and in the evening period in a sample of 10- to 12-year-old Belgian children.MethodsAccelerometer data were collected as part of the ENERGY-project in Belgium (n = 577, 10.9 ± 0.7 years, 53% girls) in 2011. Differences in total sedentary time, sedentary bouts of 2–5, 5–10, 10–20, 20–30 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
4
17
2
2
Order By: Relevance
“…Direct comparisons between the studies regarding the Breaks (breaks/hour) 11.3 ± 2.5 11.7 ± 2.4 11.6 ± 2.3 11.5 ± 2.5 11.6 ± 2.5 *p < 0.05. . The high sedentary time in the sample of the present study was mostly accumulated through bouts of short duration (< 10min), which corroborates with previous studies 9,23 . However, findings from this research revealed that Brazilian adolescents accumulate, on average, three times the sedentary time in prolonged bouts (≥ 30 min) when compared to adolescents from developed countries 9,23 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Direct comparisons between the studies regarding the Breaks (breaks/hour) 11.3 ± 2.5 11.7 ± 2.4 11.6 ± 2.3 11.5 ± 2.5 11.6 ± 2.5 *p < 0.05. . The high sedentary time in the sample of the present study was mostly accumulated through bouts of short duration (< 10min), which corroborates with previous studies 9,23 . However, findings from this research revealed that Brazilian adolescents accumulate, on average, three times the sedentary time in prolonged bouts (≥ 30 min) when compared to adolescents from developed countries 9,23 .…”
Section: Discussionsupporting
confidence: 93%
“…The high sedentary time in the sample of the present study was mostly accumulated through bouts of short duration (< 10min), which corroborates with previous studies 9,23 . However, findings from this research revealed that Brazilian adolescents accumulate, on average, three times the sedentary time in prolonged bouts (≥ 30 min) when compared to adolescents from developed countries 9,23 . In these studies, the time accumulated in sedentary bouts decreased linearly from the shortest to the longest bouts, while in our sample the decrease was observed until intermediate bouts (10-14 min), after which there were important increases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations